ANALISIS STRUKTUR, PERILAKU DAN KINERJA INDUSTRI PERBANKAN INDONESIA PERIODE 2004.1 -2011.4 - , Rini Asih Widya Hartanti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In analyzing the relationship between market structure, market behavior and performance of banks using the paradigm of Structure, Conduct and Performance (SCP). First, the traditional hypotheses based on collusive behavior, secondly, the hypothesis that differentiation based on product differentiation behavior and third, efficiency hypothesis is based on the behavior of market efficiency. The objective of this research is to examine the extent to which erformance of the banking industry in Indonesia is affected by the market structure, market behavior and other variables such as CAR and LDR. This study tries to prove that the Indonesian banking market structure supports the hypothesis of differentiation, if it is proven, then there will be a positive relationship between the Indonesian banking industry's market share with profitability. It is supportive and in line with the theory of product differentiation and the Indonesian banking run efficiently. The Results of the analysis of panel data is conducted with a sample of 111 conventional banks during the period 2004.1 to 2011.4 indicates that strongly reject the traditional hypothesis and support the hypothesis of differentiation and efficiency.